2014
DOI: 10.1128/aem.01835-14
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Analysis of the Broad-Host-Range Strain Sinorhizobium fredii NGR234 Identifies a Large Set of Genes Linked to Quorum Sensing-Dependent Regulation in the Background of a traI and ngrI Deletion Mutant

Abstract: The alphaproteobacterium Sinorhizobium fredii NGR234 has an exceptionally wide host range, as it forms nitrogen-fixing nodules with more legumes than any other known microsymbiont. Within its 6.9-Mbp genome, it encodes two N-acyl-homoserinelactone synthase genes (i.e., traI and ngrI) involved in the biosynthesis of two distinct autoinducer I-type molecules. Here, we report on the construction of an NGR234-⌬traI and an NGR234-⌬ngrI mutant and their genome-wide transcriptome analysis. A high-resolution RNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 97 publications
(115 reference statements)
3
39
0
Order By: Relevance
“…Both genes encode lactonases in NGR234, and we have previously shown that they are involved in AI degradation (21). RNA-seq data and previous studies in our laboratory suggested that these genes are expressed independently of the presence of AIs (21,44). Interestingly, the expression levels of both QQ genes were highly heterogeneous in fresh and 48-h-old cultures on a singlecell level.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Both genes encode lactonases in NGR234, and we have previously shown that they are involved in AI degradation (21). RNA-seq data and previous studies in our laboratory suggested that these genes are expressed independently of the presence of AIs (21,44). Interestingly, the expression levels of both QQ genes were highly heterogeneous in fresh and 48-h-old cultures on a singlecell level.…”
Section: Resultsmentioning
confidence: 77%
“…Our recent RNA-seq data indicate that the two QQ genes and the virB cluster encoded on pNGR234b are transcribed in an AI-independent manner and the gspD gene in an AI-dependent manner (44). This observation is interesting, since it implies that the heterogeneous regulation of genes is a more common phenomenon in NGR234 and does not depend only on the presence of AI.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations